2010
DOI: 10.1111/j.1748-1716.2010.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of haemoglobin–oxygen affinity in heterothermic vertebrates: mechanisms and biological significance

Abstract: As demonstrated by August Krogh et al. a century ago, the oxygen-binding reaction of vertebrate haemoglobin is cooperative (described by sigmoid O(2) equilibrium curves) and modulated by CO(2) and protons (lowered pH) that - in conjunction with later discovered allosteric effectors (chloride, lactate and organic phosphate anions) - enhance O(2) unloading from blood in relatively acidic and oxygen-poor tissues. Based on the exothermic nature of the oxygenation of the haem groups, haemoglobin-O(2) affinity also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 93 publications
3
80
1
1
Order By: Relevance
“…Although heterotropic ligands are known to be important modulators of Hb-O 2 affinity in vivo, the molecular mechanisms underlying the effect of temperature on Hb-O 2 affinity are much less understood (Weber and Campbell, 2011). This is surprising given that the temperature dependence of blood-O 2 affinity (whereby Hb-O 2 affinity tends to increase with decreasing temperature) was first observed more than 100years ago (Barcroft and King, 1909).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Although heterotropic ligands are known to be important modulators of Hb-O 2 affinity in vivo, the molecular mechanisms underlying the effect of temperature on Hb-O 2 affinity are much less understood (Weber and Campbell, 2011). This is surprising given that the temperature dependence of blood-O 2 affinity (whereby Hb-O 2 affinity tends to increase with decreasing temperature) was first observed more than 100years ago (Barcroft and King, 1909).…”
Section: Introductionmentioning
confidence: 58%
“…This is surprising given that the temperature dependence of blood-O 2 affinity (whereby Hb-O 2 affinity tends to increase with decreasing temperature) was first observed more than 100years ago (Barcroft and King, 1909). As with blood-O 2 affinity, temperature sensitivity varies substantially among species, with the magnitude of this effect resulting from a symphony of oxygenation-linked chemical processes that together determine the overall enthalpy of oxygenation (⌬HЈ) (Weber and Campbell, 2011). Because ⌬H O2 and ⌬H H2O are virtually invariant, variations in HЈ appear to be primarily driven by changes in endothermic contributions from oxygenation-linked effector release and/or possibly by changes in ⌬H TrR (Weber and Campbell, 2011).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…A visual inspection of the 3D structure of bovine hemoglobin (PDB code 2QSS) revealed that the side chain of the amino acid at position 27 is located at the protein surface pointing out toward the solvent, in a region that is far from the heme groups, and is not involved in intra-and/or inter-dimer contacts, or in binding to allosteric effectors (data not shown). On this basis, no functional consequences of the p.Ala27Thr substitution can be predicted according to known site mutation determinants (Storz and Moriyama 2008;Weber and Campbell 2011). The same amino acid replacement at the same position has already been detected in α-chain globin variants from goat breeds present in southern Italy (Puglia and Sardegna) (Pieragostini et al 2005;Pirastru et al 2009) and from human families in Caserta (Campania) (Lacerra et al 2004).…”
Section: Resultsmentioning
confidence: 84%
“…Studying genetic variants is also important because of the impact that single amino acid substitutions can have on protein function. A prototype example is hemoglobin, where different globin genes contribute to a protein phenotype in which amino acid replacements can affect development of a pathological state or, more generally, organism adaptation to environmental conditions, which are peculiar for the breed and/or related to the uniqueness of its products (Haenlein et al 1987;Storz and Moriyama 2008;Pieragostini et al 2010;Weber and Campbell 2011). In bovine, hemoglobin polymorphism was originally described for alleles Hb A and Hb B (Bangham and Blumberg 1958).…”
Section: Introductionmentioning
confidence: 99%